Analysis of Accountability and Transparency in the Management of School Operational Assistance Funds - Lubis, Mita Fatimah; Mais, Rimi Gusliana; Ardheta, Preztika Ayu; Mulyati, Ade; Maliki, Fanisyah (Santoso Academy Network, 2024)
This research aims to identify and analyze the application of the principles of accountability and transparency in the management of BOS (School Operational Assistance) funds at SMP Negeri 149 Jakarta. The method used is qualitative descriptive, which describes what happens in a particular situation, field, or area. This research was conducted at SMP Negeri 149 Jakarta, located in Cipinang Besar Selatan, Jatinegara District, East Jakarta City, DKI Jakarta Province. In this study, data was obtained through observation and direct interviews with the Principal, BOS fund operator, teachers, and the School Committee. Data analysis was conducted using data reduction and data presentation. The results and discussion indicate that the application of the principle of accountability in the management of BOS funds at SMP Negeri 149 Jakarta includes the planning of BOS funds, implementation and use of BOS funds, and reporting and accountability of BOS funds. The BOS fund management has been running well and in accordance with the technical regulations for BOS fund management. The application of the principle of transparency in the management of BOS funds at SMP Negeri 149 Jakarta has been carried out, with the involvement of teachers and staff in the BOS management team in determining the budget for school activities and the teaching and learning process. However, the school's website is inactive, so the dissemination of information related to the school has not been well communicated.